“Não comprometidos”: o Movimento dos Países Não-Alinhados nas páginas do jornal O Estado de S. Paulo em 1961 - Espósito, Fábio Adorno (2019)
The present work aims to expose and understand how the newspaper O Estado de S. Paulo approached the Non-Aligned Movement in 1961. In it, we first tried to explain how the international system was organized during the Cold War, their characteristics, and what can be considered as major crises and events in terms of international politics during the year. We then present and describe O Estado de S. Paulo as a newspaper in 1961, as a historical source used for research, and we explain in what is inspired our method of discourse analysis, in which we base ourselves precisely to analyze the discourse of the newspaper. In Chapter 3 we treat specifically with the Non-Aligned Movement, its processes of formation and institutionalization, and in which we highlight the Conference of Heads of State and Government of Non-Aligned Countries (Belgrade Conference), which brought together the twenty-five founder members (in addition to three observer countries) and generated what is considered the founding document of the movement: the Belgrade Declaration - also analyzed in the research. The last chapter is the analysis and description itself of how the newspaper O Estado de S. Paulo approached the Movement of Non-Aligned Countries in 1961, with its main characteristics, approaches and criticisms